The complications of bones surgery in Veterinary Medicine - ΖΩΛΟΣ Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author is exposing his thaughts for facing the complications of bones surgery. It is difficult to face with these complications but if a special treatment and a good technique are chosen it is possible to give a good help.